Temporal variations in air permeability and soil CO2 flux in volcanic ash soils (island of Vulcano, Italy). (13th August 2017) - Camarda, Marco; Prano, Vincenzo; Cappuzzo, Santo; Gurrieri, Sergio; Valenza, Mariano
Abstract: Air permeability is a major physical factor affecting the advective transport of a gas through the soil, and variations in this parameter can strongly influence the emission of endogenous gases from the soil to the atmosphere. In this paper, we illustrated a new and simple method for measuring in situ air permeability based on the measurement of air pressure inside a special probe inserted into the soil. The method was designed and developed primarily to study the relationship between air permeability and the soil CO2 flux in an active volcanic area. The method was used for continuous monitoring of the air permeability at two different locations on the island of Vulcano. At the same time, the values of the atmospheric pressure, temperature, rain, and volumetric water content of the soil were also acquired to investigate their effect on soil air permeability and soil CO2 flux. The results showed that during the monitoring period, soil air permeability exhibited minor variations at each site, while larger variations in the soil CO2 flux were recorded. The effect of soil air permeability on soil CO2 flux was negligible at both sites, whereas a strong dependence of soil CO2 flux on volumetric water content and on atmospheric pressure was found. Furthermore, the variation in air permeability recorded at both sites was much lower than that predicted using some well‐known predictive models, showing that the relationship among different soil transport parameters is more complex in real field conditions than would be expected by semiempirical models. Key Points: Temporal variation in soil air permeability recorded at both sites has a slight influence on variations in the soil CO2 flux Soil CO2 fluxes of organic origin are strongly influenced by changes in VWC Soil CO2 fluxes of volcanic origin are strongly influenced by changes in atmospheric pressure